UJI AKTIVITAS ANALGESIK FRAKSI DAUN SENGGANI (Clidemia hirta [L] D.Don) PADA MENCIT PUTIH GALUR SWISS WEBSTER - Taufik Septiyan Hidayat; Dadan Rohdiana; Syumillah Saepudin; Dini Febrianty; Yunita Al Azzahra (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Pain is a sensation that can interfere with activities and reduce the quality of life of the sufferer if left untreated and left prolonged. Senggani is one of the plants that contains flavonoid compounds and steroids that have analgesic activity. This study aimed to test the analgesic activity of senggani leaf fraction (Clidemia hirta [L] D.Don) in white mice swiss webster strain induced acetic acid and determine the fraction that most effectively produces analgesic activity. The type of research conducted is true experimental design based on Complete Randomized Design (RAL). The test animals used were 25 heads divided into 5 groups with 5 replications, namely negative control (CMC 1%), positive control (dexamethasone) and the test group of senggani leaf fraction, namely n-hexane, ethyl acetate, and ethanol fractions. The data obtained were analyzed using an alternative test from One Way ANOVA namely Kruskal Wallis with a follow-up test post hoc Mann Whitney test. The results showed that the fraction of senggani leaves in all types of solvents had analgesic activity compared to negative controls (CMC 1%) with a significant difference (p0.05). From these results it is concluded that the senggani leaf fraction can be used as an analgesic.